Densification of the entropy stabilized oxide (Mg0.2Co0.2Ni0.2Cu0.2Zn0.2)O. Issue 10 (August 2022) - Jacobson, V.; Gann, K.; Sanders, M.; Brennecka, G.
Abstract: The first entropy-stabilized oxide, (Mg0.2 Co0.2 Ni0.2 Cu0.2 Zn0.2 )O, was reported in 2015. Initial studies synthesized this material using solid state processing and were limited to densities < 80%. Here, we report a straightforward solid state route to sinter samples to densities up to 98% of the theoretical by identifying the role of oxygen and promoting the resulting mechanisms in densification. Previous works have studied effects of cation stoichiometry on the entropy-driven reaction to form a single phase, but few have explored the associated effects of anion stoichiometry and/or redox chemistry on both phase stability and densification. We demonstrate here that tuning heating rate and p O2 during heating of initially-homogeneous calcined powders can enhance densifying diffusion processes and enable reliable sintering of dense Mg0.2 Co0.2 Ni0.2 Cu0.2 Zn0.2 )O samples.